2022
DOI: 10.1108/jadee-02-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Gendered impact of COVID-19 on consumption of perishable and nonperishable food commodities in Pakistan

Abstract: PurposeCovid-19 is a serious threat to the dietary quality of vulnerable communities in developing countries with limited economic resources. This study explored the implications of COVID-19 on daily dietary behavior and food consumption patterns of perishable and nonperishable food commodities based on the gender of household headship in Pakistan.Design/methodology/approachThe data was collected through an online survey using the snowball sampling technique. A mixed design ANOVA, an independent t-test and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…According to studies conducted in Sub-Saharan Africa, lowering dietary variety, as well as modifying the quality and amount of foods ingested owing to the COVID-19 lockdown, was a prevalent approach for households to manage rising basic food costs [ 37 ]. In Pakistan, study findings revealed that COVID-19 had a greater impact on the diet diversity of female households than male households, resulting in the lower intake of specific nutrients and lower overall consumption of perishable and non-perishable food commodities, such as meat and meat products, in the former group [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to studies conducted in Sub-Saharan Africa, lowering dietary variety, as well as modifying the quality and amount of foods ingested owing to the COVID-19 lockdown, was a prevalent approach for households to manage rising basic food costs [ 37 ]. In Pakistan, study findings revealed that COVID-19 had a greater impact on the diet diversity of female households than male households, resulting in the lower intake of specific nutrients and lower overall consumption of perishable and non-perishable food commodities, such as meat and meat products, in the former group [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that the outbreak of the COVID-19 pandemic could change consumers' purchasing behaviour. Previous literature, such as Shahbaz et al (2022) explored the impact of COVID-19 on the consumption of perishable and nonperishable food commodities in Pakistan. They found that female-headed households decreased their intake of dairy products of perishable and non-perishable food commodities compared to male-headed households during the COVID-19 pandemic.…”
Section: Covid-19 and Poultry Industrymentioning
confidence: 99%
“…Other studies have also investigated how the emergence of the COVID-19 pandemic has influenced consumer behaviour (Shahbaz et al, 2022;Tan et al, 2022;Ben Hassen et al, 2021;Kahtun et al, 2020;Attwood & Cother, 2020), the supply chain of food (Min et al, 2020), and affected other sectors of the world's economy (Kartari et al, 2021;Rolfe et al, 2021;Biswal et al, 2020;Ogier et al, 2020;Patil & Patil, 2020;Zhang et al, 2020). However, no study has specifically examined how consumers' motivations and perceptions of COVID-19 have affected the consumption of local poultry, especially chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The study findings indicated that households began to consume more snacks and dairy products and reduced their intake of vegetables and fruits during the pandemic. In Pakistan, Shahbaz et al [46] studied the impact of COVID-19 on the daily intake of perishable and nonperishable commodities and found that the intake of perishable food commodities decreased more during the pandemic than non-perishable foods due to COVID-19. Maestre et al [47] also noted a decline in the consumption of fresh food commodities and an increase in sweets and snacks during the public health measures imposed to curb the spread in Spain.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%